Farmers’ Perceptions, Knowledge and Practices for Nematode Management in Tomato Farms at Meghang, Nuwakot - Begam, Chandani; Shrestha, Subeksha; Oli, Asmita; Poudel, Aayushma (Nepalese Journal of Agricultural Sciences, 2026)
This study was carried out in Meghang Rural Municipality, Nuwakot, Nepal, to assess farmers’ knowledge, perceptions, and practices regarding nematode management in tomato cultivation. The research was conducted from April 28 to June 20, 2025, covering the tomato cropping cycle to observe nematode symptoms, progression, and management outcomes. The Primary data were collected through field visits and semi structured interviews using a simple random sampling method. A total of 100 tomato growers were selected across different wards. Findings revealed that 79% of farmers considered nematodes a growing problem, and average yield loss was reported to be 30%. Only 17% of farmers demonstrated high knowledge of nematode management. Traditional practices such as application of animal manure were most common (67%), while integrated pest management (IPM) was rarely practiced. Some farmers adopted crop rotation with onion, garlic, and legumes, common trap crops used by farmers was marigold, velvet been and rapeseed. A few used grafted seedlings as a management strategy. Field monitoring was weak, with less than 27% of farmers conducting regular inspections. Chemical control was widely adopted (88%), yet only 12% of farmers rated it as highly effective. Awareness of IPM was particularly low, with 80% reporting insufficient knowledge. Farmers have limited awareness and low adoption of sustainable nematode management practices. Capacity building, farmer training on IPM, promotion of resistant varieties and grafted seedlings, and improved access to non-chemical alternatives are urgently required. Strengthening institutional support can help minimize nematode related yield losses and improve tomato productivity.